EFEKTIVITAS POSTING VIDEO "GERAKAN CUCI TANGAN YANG BENAR" TERHADAP PERBAHAN PERILAKU KESEHATAN MENCUCI TANGAN FOLLOWERS AKUN TIKTOK @ALODOKTER.ID DALAM PENCEGAHAN COVID-19 - Davin Risy Al Hanif (2023)
The correct hand washing techniques are one of many ways to prevent the spreads of Covid-19. Because of that, Alodokter Indonesia have tried to give health education through new media with "The Correct Hand washing Techniques" video post on @Alodokter.ID's TikTok account. This research aims to find the effectiveness of "The Correct Hand washing Techniques" video post using new media theory and Cyber Health Communication Model. Quantitative explanative method was used in this study to examine this research sample which consists of 100 @Alodokter.ID's TikTok followers. Sampling was done with purposive, nonprobability sampling using questionnaire which distributed using Google Form. The result of this study found that the research hypothesis proves that H_0 is rejected and H_a is accepted: "The Correct Hand washing Techniques" video post is effective to change the hand washing health behavior of @Alodokter.ID's TikTok followers, but only up to attitude changes stage with coefficient correlations value of 0,589 which categorized as "moderate" and positive regression value of 0,694.